(3eYQaI GdeLQhMjf ef GdeMOKjfs - (3eMeO Hf MHGf Hf CMeO Hf MHGf Hf eYGP Hf eYHO GdJejej, CHh MGJe GdHSJj, hjbGd dg GHf MHGf,J (B354 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdCMO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B173s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B273 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B256 - (3U (B997 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(19598(3H(B) s
Keywords: (3GdJGQjNs